Histomorphological pattern of lesions of cystoscopic bladder biopsies in a tertiary center in Nepal- A retrospective descriptive study (Journal of Pathology of Nepal, 2022)
Background: Bladder cancer accounts for 3% of all cancer diagnoses and is one of the most common cancers worldwide. Bladder tumors have different subtypes and behavioral patterns. This study is performed in the pathology department of Shree Birendra Hospital. It is a data review done on cystoscopic bladder biopsy results for the past 5 years to study the histomorphological patterns of various bladder lesions.Materials and Methods: This is a descriptive cross-sectional study done on cystoscopic bladder biopsy results. A hospital register-based retrospective study was conducted on the data of five years duration. The epidemiological parameters were calculated using Microsoft Excel.Results: A total of 56 cystoscopic biopsies were performed during the study period of 5 years. Among them, 45(80.36%) were male and 11(19.64%) were female. The peak incidence was seen in the age group 70-79 years (26.78%). The majority of the patients had neoplastic lesions (83.92%). The peak incidence of neoplastic lesions also belonged to the age group 70-79 years (31.19%). The most common malignant lesion was papillary urothelial carcinoma i.e. 45 cases (95.74 % among the neoplastic lesions and 80.36% among all the total bladder lesions)Conclusions: Among the bladder lesions that have undergone cystoscopic biopsies, urothelial carcinoma is the most common with male predominance. The early and definitive diagnosis with accurate grading and staging of bladder tumors can be done by histopathology. Early identification of bladder tumors has an impact on the therapeutic approach as well.